ASSESSMENT OF LEVEL OF STRESS AND COPING BEHAVIORS STRATEGIES AMONG STUDENTS AT THE COLLEGE OF NURSING AT THE UNIVERSITY OF SULAIMANI - Abdalla, Sarbaz Mustafa (Journal of Sulaimani Medical College, 2022)
Background Stress is the emotional and physical strain caused by our response to pressure from the outside world. It is almost impossible to live without stress, but if the stress gets out of control, it may harm well-being, health, relationship and enjoyment of life. Students are subjected to different stressors such as the pressure of academics with an obligation to succeed, an uncertain future and difficulties of integrating into the system. Other ways of coping have been found to be more or less adaptive. Objectives The general aim of the study is to assess the levels of stress among nursing students and how they cope with stressors at the College of Nursing at the University of Sulaimani. Materials and Methods Data was collected from 85 nursing students. Nursing from all stages. A modified Perceived stress scale and brief coping inventory were used to collect data. SPSS version 21 with Chi-square and Fisher exact test for association was used for data analysis. Results The study revealed that the majority of the sample (81.4%) had a moderate level of stress, while most of them (83.7%) used high levels of coping strategies. Conclusion The study revealed a strong relationship between levels of stress and coping strategies used by the participants.
Keywords: Assessment; Stress; Coping